RESPON KOMBINASI PUPUK KCl DAN PUPUK ORGANIK CAIR (POC) SABUT KELAPA TERHADAP PERTUMBUHAN JAGUNG MANIS (Zea mays saccaharata Sturt) DI TANAH GAMBUT - Zahlul Ikhsan; Intan Sari; Suryadi Suryadi; Dede Suhendra (JURNAL AGROPLASMA, 2020)
This This study aims to determine the best dose of KCl Fertilizer and Liquid Organic Fertilizer of coconut coir on the growth of sweet corn (zea mays saccaharata Sturt) in peat soils. This study used a non factorial randomized block design with 6 treatments and 4 replications. The treatments used were 100 kg KCl fertilizer, POC Coconut Fiber 30 ml / liter, 100 kg KCl + POC coconut coir fertilizer, 75 kg KCl + POC coconut coir fertilizer, 50 kg KCl + POC coconut coir fertilizer, 25 kg KCl + POC fertilizer coconut fiber. The parameters observed were plant height, number of leaves / plants, leaf area index, stem diameter, emergence, male and female flowers, observational data were analyzed using analysis of variance (ANOVA) and continued with HSD tukey test at 5% confidence level. Based on the results of research that has been carried out, all treatments did not show a real effect on all parameters. Provision of coconut milk POC 30 ml / water gives the best results on the growth of sweet corn. Keywords: KCl fertilizer, liquid organic fertilizer, sweet corn